The Unusual Case of BYJU’s : Creating One of the World’s Most Valued Educational Technology Companies from India - Rajan, Thomason (Indian Journal of Marketing, 2022)
Byju Raveendran started taking classes for CAT aspirants in 2003. What started as a coaching class grew in size and scale, and BYJU’s became one of the world’s most valued educational technology companies built from scratch in India. Once the number of students started growing, the company faced issues in scaling up. A chance encounter with friends planted the seeds of starting a business; another unexpected meeting with an investor helped the company pivot its offerings. Backed with funding from a list of top global investors and at very high valuations, BYJU’s story is an unusual one in the Indian context. The case discusses the critical elements of the journey, including the role of the student team that built the business, the product development process, the sales challenges, marketing efforts, and key acquisitions that helped drive growth.